A potential functional association between mutant BMPR2 and primary ovarian insufficiency (2017)
Primary ovarian insufficiency (POI) affects ~1% of women in the general population. Despite numerous attempts at identifying POI genetic aetiology, coding mutations in only a few genes have been functionally related to POI pathogenesis. It has been suggested that mutant BMPR2 might contribute towards the phenotype. Several BMP15 (a BMPR2 ligand) coding mutations in human species have been related to POI pathogenesis. The BMPR2 p.Ser987Phe mutation, previously identified in a woman with POI, might therefore lead to cellular dysfunction contributing to the phenotype. To explore such an assumption, the present study assessed potential pathogenic subcellular localization/aggregation patterns associated with the p.Ser987Phe mutant form of BMPR2 in a relevant model for studying ovarian function. A significant increase in protein-like aggregation patterns was identified at the endoplasmic reticulum (ER) which permitted us to establish, for the first time, a potential functional association between mutant BMPR2 and POI aetiology. Since BMPR2 mutant forms were previously related to idiopathic pulmonary arterial hypertension, BMPR2 mutations may be related to an as-yet-to-be described syndromic form of POI involving pulmonary dysfunction. Additional assays are necessary to confirm that BMPR2 abnormal subcellular patterns are composed by aggregates. Abbreviations: POI: primary ovarian insufficiency; ER: endoplasmic reticulum; NGS: next generation sequencing. © 2017 Taylor and Francis.